SPAWNING AND DEVELOPMENT OF DOG CONCH Strombus sp. LARVAE IN THE LABORATORY - . Muzahar; Agus Alim Hakim (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2018)
An intensive exploitation of dog conch Strombus sp. in Tanjungpinang city coastal waters has occurred because the increasing number of fishermen, population growth and demand. In addition, the increasing activities of bauxite mining cause the declining in quality of waters around dog conch, thus providing ecological pressure that endangers sustainability of the dog conch. The purpose of this study was to observe the spawning and development of dog conch in the laboratory. Spawning was done in aquarium with 100 liters of seawater (salinity: 26±1 ppt), with stimulation of spawning performed by changing 90% water volume every day until the female issued the eggs. The female issued the eggs on the third and fourth days of stimulation. Eggs are attached to the wall of the aquarium. Egg cell division occurs after about 2 hours of the egg is released the mother, from one cell into two cells and a row into four cells, eight cells, the sixteen cells, thirty-two cells to multicellular. The embryo develops into a gastrula phase than trochophore phase. Larvae were reared in a tank containing 20 liters of seawater (salinity: 26±1 ppt). Veliger larvae occurred on the fifth day until the eleventh day. Veliger larvae are planktonic, and turn into benthic with a sedentary life in the bottom waters to begin the formation of a thin and transparent shell. The value of water quality parameters during maintenance category feasible: DO of 7.6 to 7.8 mg / L; pH of 8.13 to 8.33; turbidity of 1.97 to 3.90 NTU, salinity of 26.8 to 27.8 ppt; and temperature of 25.8-27.8°C.